PURWARUPA SISTEM PENGENDALIAN DAN AKUISISI DATA PADA RUMAH CERDAS BERBASIS SMARTPHONE - Ryan Maulana; Wahyudi Wahyudi; Muhammad Arfan (Transient: Jurnal Ilmiah Teknik Elektro, 2022)
Internet of Things (IoT) is the latest technology that has an extraordinary role in improving the quality of life and developing the world economy. IoT also known at community widely which is used to support global connectivity in various sectors, one of them is the smart home. Smart home is a new way in home appliances or equipment such as a lamp, air conditioner, heater and gate which is that equipment can be controlled remotely via the internet with the Human Machine Interface (HMI) system. On this final project, a prototype control and data acquisition system is designed for smart home based on smartphone. The system is designed using ATMega2560 and ESP8266 microcontrollers along with supporting sensors, while the HMI system is designed based on Android which can perform the functions of Supervisory Control and Data Acquisition (SCADA) namely measuring physical quantities (telemetering), notification of alarming systems (tele-signaling) and controlling home appliances easily and efficiently via the internet (tele-controlling). Sending and receiving data by the microcontroller to the server has an interval of 889 ms. The success rate and communication speed are influenced by internet connection and data traffic on the server. The data obtained in the telemetering system corresponds to the real situation of the smart home prototype. Tele-controlling and tele-signaling systems work well when operated.